Aromatic sulfonation with sulfur trioxide: mechanism and kinetic model. Issue 1 (19th September 2016) - Moors, Samuel L. C.; Deraet, Xavier; Van Assche, Guy; Geerlings, Paul; De Proft, Frank
Abstract : Electrophilic aromatic sulfonation of benzene with sulfur trioxide is studied with ab initio molecular dynamics simulations in gas phase, and in explicit noncomplexing (CCl3 F) and complexing (CH3 NO2 ) solvent models. Abstract : Electrophilic aromatic sulfonation of benzene with sulfur trioxide is studied with ab initio molecular dynamics simulations in gas phase, and in explicit noncomplexing (CCl3 F) and complexing (CH3 NO2 ) solvent models. We investigate different possible reaction pathways, the number of SO3 molecules participating in the reaction, and the influence of the solvent. Our simulations confirm the existence of a low-energy concerted pathway with formation of a cyclic transition state with two SO3 molecules. Based on the simulation results, we propose a sequence of elementary reaction steps and a kinetic model compatible with experimental data. Furthermore, a new alternative reaction pathway is proposed in complexing solvent, involving two SO3 and one CH3 NO2 .